Thirty-Day Acute Health Care Resource Utilization Following Outpatient Anterior Cruciate Ligament Surgery. Issue 8 (November 2018) - Liu, Jiabin; Kim, David H.; Maalouf, Daniel B.; Beathe, Jonathan C.; Allen, Answorth A.; Memtsoudis, Stavros G.
Abstract : Background and Objectives: The need for hospital-based acute care following outpatient surgical procedures is expensive and measured as marker for quality. However, little information is available about events leading to emergency department visit or inpatient admission after ambulatory anterior cruciate ligament (ACL) surgery. Methods: We studied adult patients who underwent outpatient ACL surgery in New York State between 2009 and 2013 using the Healthcare Cost and Utilization Project database. Emergency department visits and inpatient admissions within 30 days of surgery were identified by cross-matching 2 additional independent Healthcare Cost and Utilization Project databases. Results: The final cohort included 26, 873 subjects. We identified 1208 (3.90%; 95% confidence interval [CI], 3.6%–4.1%) secondary health care encounters of interest. The majority of these encounters were emergency department visits (951). The most common reasons were musculoskeletal pain (349 [28.9%]), any infection (122 [10.1%]), drug abuse (98 [8.1%]), wound infection (87 [7.2%]), deep venous thrombosis (77 [6.4%]), and psychotic events (54 [4.5%]). Patients operated on in high-volume surgical centers were less likely to require acute care (odds ratio, 0.47; P < 0.001; 95% CI, 0.34–0.63), whereas Medicare/Medicaid patients carried higher odds (odds ratio, 2.52; 99% CI, 2.07–3.07). Conclusions: The rate of hospital-based acute care following outpatient ACL surgery was 3.90%. Many of the events were expected complications related to surgery, such as infection and deep venous thrombosis. However, musculoskeletal pain, drug abuse, and psychotic events featured more prominently than expected. Our findings may direct efforts to address these reasons for seeking acute care after ACL surgery, reduce cost, and improve quality of care. Abstract : Supplemental digital content is available in the text.